KONSTITUSIONALITAS PASAL 222 UU NOMOR 7 TAHUN 2017 TENTANG PEMILU (PRESIDENTIAL TRESHOLD) - Syahuri, Taufiqurrohman; Fahrozi, Muhammad Helmi (AL WASATH Jurnal Ilmu Hukum, 2020)
The President and Vice Presidential election in Indonesia is manifestation of people’s sovereign. In that regards, it mechanism should be implemented in accordance with the UUD 1945 Constitution and be based on democratic values. This paper explores the role of Constitutional Court in settling the dispute on presidential treshold. This paper examines the relevancy between Art. 6A paragraph 1 UUD 1945, The role of Constitutional Court, and democratic values on the implementation of presidential treshold. In short, this paper analyzed the constitutionality of Art. 222 UU 7/2017 Election Law.